Solubilization of Insoluble and Poorly-Water Soluble Drugs in Micellar Systems - GÖKTÜRK, SİNEM (My University, 2024)
Introduction:This study investigates the micellar solubilization of several insoluble and poorly soluble drugs—clopidogrel bisulfate, ganciclovir sodium, miconazole nitrate, brinzolamide, brimonidine tartarate, and dexamethasone—using sodium dodecyl sulfate (SDS), aerosol-OT (AOT), dodecyl trimethylammonium bromide (DTAB), and cetyltrimethylammonium bromide (CTAB) as surfactants.Methods: The micellar solubilization experiments were conducted by preparing solutions of the drugs in the presence of SDS, AOT, D TAB, and CTAB micelles. Spectrophotometric measurements were performed at a constant temperature of 298 K to analyze the solubilization efficiency of each surfactant. Phase-solubilization graphs were plotted to visualize the relationship between drug solubility and surfactant concentration.Results: The results indicated that hydrophobic interactions play a critical role in surfactant solubilization powe r. AOT was identified as the most effective surfactant among those tested. The solubility tendencies of the drugs in the presence of micelles were discussed based on the calculated KM values and the spectral behavior of drug molecules.Conclusion: Micellar solubilization offers a promising approach to characterize drugs with varying solubility profiles—ranging from slightly soluble to insoluble in water. Additionally, surfactant micelles serve as effective biomimetic models for membrane systems in pharmaceutical research. the findings from this study hold implications for drug formulation and design, particularly in addressing solubilization challenges and optimizing pharmaceutical dosage forms. Keywords: Surfactant, poorly soluble drugs, critical micelle concentration, micelle, solubilization
Keywords: Kimya; Temel Bilimler; Chemistry; Natural Sciences; Temel Bilimler (SCI); Doğa Bilimleri Genel; ÇOK DİSİPLİNLİ BİLİMLER; Natural Sciences (SCI); NATURAL SCIENCES, GENERAL; CHEMISTRY; MULTIDISCIPLINARY SCIENCES; Kimya (çeşitli); Genel Kimya; Multidisipliner; Fizik Bilimleri; Chemistry (miscellaneous); General Chemistry; Multidisciplinary; Physical Sciences; Surfactant; poorly soluble drugs; critical micelle concentration; micelle; solubilization